PENGARUH PENAMBAHAN SERBUK BUNGA ROSELLA (Hibiscus sabdariffa L) TERHADAP WARNA, RASA DAN AROMA YOGHURT SUSU KAMBING - Puji Rahayu; Doso Sarwanto; Sari Tuswati; Yanita Viastika; Tasnin Mohamed (Fakultas Peternakan. Unwiku, Purwokerto, 2025)
This study aims to determine the effect of the addition of rosella flower powder (Hibiscus sabdariffa L) on the color, taste and aroma of goat's milk yogurt. The ingredients used are goat's milk, rosella flowers, and yoghurt starter. The design of this study used an experimental method with a Complete Random Design (RAL) unidirectional pattern consisting of four treatments, namely P0 (control), P1 (addition of rosella flower powder 5 grams/200ml goat milk + yoghurt starter 20%), P2 (addition of rosella flower powder 10 grams/200ml goat milk + yoghurt starter 20%), and P3 (addition of rosella flower powder 15 grams/200ml goat milk + yoghurt starter 20%). Each treatment consisted of five replicates. The parameters measured were color, taste and aroma using 25 semi-trained panelists. The results of the study proved that the addition of rosella flower powder (Hibiscus sabdariffa L) had a very real effect (P<0.01) on the color and taste of goat milk yogurt and had no real effect (P>0.05) on the aroma of goat milk yogurt. The P3 treatment was the most preferred color assessment treatment by the panelists because rosella flowers contained anticionin, which is a red pigment